Factors affecting women's career and advancement in selected public high school in Iloilo City - Bito-on, Sarah Therese; De la Pena, Francesca May.; Doronila, Charry Joy. (2006.)
This research study attempts to determine the factors that affect women's career advancement in selected public high schools in Iloilo City. In the process of answering the said problem, the study also aimed for the following : (1) describe how women regard themselves as the head or the principal of the school; (2) describe how subordinates (both male and female) evaluate their female school head; (3) determine the problems encountered by women as school heads/principals in attaining top-level positions; (4) describe issues and concerns affecting women's success in the field of management; and (5) determine the leadership styles of the female heads or principal use. The researchers randomly selected five (5) public high schools in Iloilo City. Thus, five (5) female school heads/principals were the primary respondents. Moreover, four (4) subordinates for each principal were also the subject for this study in order for the researchers to describe the perception regarding women as leaders. Primary data was obtained through survey questionnaires consisted of questions that helped to reveal the perceptions of respondents regarding women as leaders. The results of the study have shown that the factors that could affect the career advancement of female school heads/ principals in could be the following: (1) their qualifications in their said position, (2) the technical, psycho-social, and rational skills they possess, (3) how they lead and interact with their peers/subordinates, and (4) issues and concerns like sexual harassment and gender discrimination in their work environment. In view of the research results, discussion, and conclusions, the following recommendations are forwarded : (1) for future studies, it is advisable that the questionnaires for the subordinates should be given directly to them to avoid biases since there is a tendency that the subordinates cannot express themselves freely in fear of being confronted by their leaders, (2) for future researchers, they should prepare themselves in whatever shortcomings they would face while conducting the study, and (3) for women leaders, they should possess technical, psycho-social, and rational skills for them to be effective leaders.
Research Paper (Mgt 199-Management Research). -- Iloilo City : University of the Philippines in the Visayas-College of Management, October 13, 2006.